Identification and authentication as the basis for information protection in computer systems - Arutyunov, V. V. (Scientific and technical information processing, 2012)
Basic methods for user authentication and their features when performing access to computer systems are considered. They include password protection, authentication hardware, and biometric authentication, as well as determining the identity of access subjects by using their coordinates. Modern avenues of research into information protection are discussed.